(untitled) (The Research of Medical Science Review, 2025)
Objective This study aims to find the association of age, working status, and training related to sterilization and infection control with their knowledge, attitude and practice categories. Methodology A total of 100 participants were conveniently selected. Our inclusion criteria are those health care workers who have working experience in operation theater. Those who did not have operation theatre exposure or were absent on the day of data collection were excluded from the study. Data was analyzed with the help of SPSS-version 25. Results Upon correlating age with knowledge, practices, and attitude categories, no statistically significant association has been found with P values 0.676, 0.214 and 0.848 respectively. Working status has association with all three categories with a P value of <0.001 in all categories respectively. Receive training for sterilization and infection control shows association with knowledge (P =0.004). While for others remaining categories results were insignificant with a P value of >0.05. Conclusion In conclusion, healthcare professionals have a good level of knowledge about infection control. Further gaps can be filled by regular training sessions and hands on practices workshops. Hospital administration needs to place a high priority on ongoing education programs designed to fulfill specific job roles. Ultimately, patient outcomes, staff health, and healthcare costs will be improved.